LOCAL KNOWLEDGE AND DRIVERS OF HUMAN-PRIMATES CONFLICTS AROUND COMOE NATIONAL PARK, NORTHEASTERN COTE D’IVOIRE - Coulibaly Tchinyo; Ouattara Karim; Kouao Marthe Lydie; Ouattara Amara; Koné Inza (Journal of Animal and Plant Sciences, 2025)
Human activities near Comoé National Park are leading to conflicts with wild animals, especially primates. They leave the park seeking food and shelter in nearby farming sites, which impedes efforts for sustainable conservation and management. In this context, a better understanding of indigenous knowledge may inform strategies for mitigating and resolving human-primate conflicts. This study aimed to understand local knowledge of human-primate conflicts, categorize them, and identify contributing factors. Data was collected in September 2022 from 502 participants, including residents, hunters, and park managers, using focus group discussion (n = 115) and semi-structured questionnaire (n = 387) in 35 localities around Comoé National Park. Findings revealed that primate species like patas monkey (Erythrocebus patas) (99.0%), green monkey (Chlorocebus sabaeus) (87.8%), and olive baboon (Papio anubis) (82.9%) are well-known among respondents due to their proximity to riverine areas. Primates are culturally significant for the Koulango, Lobi, and Malinké ethnic groups, who use them mainly for food, medicine, and spiritual purposes. Non-human primates, notably patas monkey (Erythrocebus patas) (98.9%), green monkey (Chlorocebus sabaeus) (36.1%), olive baboon (Papio Anubis) (6.5%), and white-naped mangabey (Cercocebus lunulatus) (2.7%), were identified as crop raiders by farmers. This study identified ten crops affected by primate foraging, with the most damaged ones being yam (Dioscorea spp) (80.1%), maize (Zea mays) (75.6%), and cassava (Manihot esculenta) (65.8%) cultivated at park vicinity. Most local communities use traps (90.3%) and watch guarding (79.1%) to prevent crop damage from primates. Factors such as crop types, proximity of farms and reduction of food availability in the park are translated by the monkeys' exit from the park for the surrounding plantations. Preserving the natural habitats of primates reduces human-primate conflicts by keeping animals out of riparian farms.
Keywords: Local community; Primates; Conflicts; Crop raiding; Comoé National Park; Côte d’Ivoire.